An ontology of controversial terms at the core of the systems life cycle. (7th July 2014) - Rao, Lila; Mansingh, Gunjan; Duggan, Evan W.
The information system (IS) discipline has been plagued by the absence of agreed definitions of the numerous terminologies that are used throughout the range of processes and activities employed to deliver applications for productive use. This lack of agreement also has constraining implications for cumulative research in the discipline. In this paper, we propose a solution to the problem that involves the development of a formal IS domain ontology using a methodology that focuses on ensuring the completeness and consistency of the ontology. The ontology provides a mechanism for standardising the vocabulary in the domain, classifying concepts and terms, representing relationships, identifying synonyms and homonyms, and it identifies the instances of these concepts and relationships. Our solution will facilitate knowledge sharing in the information systems community and further scholarly activities which require a deeper understanding of the structure of information in this domain.